2022
DOI: 10.3892/ol.2022.13610
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of second primary malignancies among first primary malignancy survivors: A single‑center study, 2005‑2020

Abstract: The cancer survivor population is growing due to advances in detection and treatment. For improved long-term patient management, it is critical to examine the clinical characteristics and outcomes of second primary malignancies (SPMs). An SPM is defined as a second distinct pathological diagnosis, with the same or different origin as the first primary malignancy (FPM). In the present retrospective study, categorical clinical variables were compared between subgroups and the impact on overall survival was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The development of MPCs is associated with various factors 10,37 . Lifestyle behaviors, including smoking and excessive alcohol consumption, contribute to the development of MPCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of MPCs is associated with various factors 10,37 . Lifestyle behaviors, including smoking and excessive alcohol consumption, contribute to the development of MPCs.…”
Section: Discussionmentioning
confidence: 99%
“…34,36 The development of MPCs is associated with various factors. 10,37 Lifestyle behaviors, including smoking and excessive alcohol consumption, contribute to the development of MPCs. Moreover, common environmental exposures, including environmental pollution, occupational exposures, and infections, contribute to the development of subsequent cancers.…”
Section: Metachronous Interval Time (Years)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the neoplasm level, we also identified a number of ADEs with strong signal values. Second primary malignancy (SPM) (n = 43,) is defined as a second, distinct pathological diagnosis of the same or different origin as the first primary malignancy, and chemotherapy also increases the risk of secondary hematologic or solid malignancies (Lenzi et al, 2020;Geng et al, 2023). The mechanism of etoposide-induced second primary malignancy (SPM) can be attributed to two possible explanations.…”
Section: Neoplasms-related Adverse Reactionsmentioning
confidence: 99%
“…Evidence shown that breast cancer survivors are especially vulnerable to secondary cancers [ 3 ], with 2.5-fold increased odds of developing colorectal cancer (CRC) compared to those without a history of cancer [ 3 ]. This may be attributed to the carcinogenetic effects of primary-cancer related treatment (e.g., chemotherapy or radiation) [ 4 ], genetic predisposition [ 5 ], and personal behaviors [ 6 ]. However, the development of secondary CRC after breast cancer can be a life-threatening event for breast cancer survivors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%